OPTIMALISASI DONOR DARAH SUKARELA UNTUK MENDUKUNG KETERSEDIAAN DARAH DI MASYARAKAT - Pujilestari, Intan; Monica , Rizqy Dimas; Rahayu , Ayu Hendrati; Suharto, Suharto; Trianto, Wowo (ASOSIASI IDEBAHASA KEPRI, 2026)
The availability of safe and sustainable blood is an important component in the health care system. Voluntary blood donation is the main source of meeting blood needs in society, however the level of donor participation still faces various obstacles, such as lack of awareness, limited access, and lack of appropriate education. Therefore, optimizing voluntary blood donations needs to be carried out in a planned and sustainable manner. This optimization includes increasing education and outreach to the public regarding the benefits of blood donation. In addition, cooperation between the government, Indonesian Red Cross, educational institutions and the private sector is very necessary to expand the reach of blood donation activities. Improving service quality also plays an important role in creating a positive experience for donors thereby encouraging repeat participation. Providing non-material appreciation to voluntary donors can provide additional motivation without eliminating the human value of blood donation activities. By implementing a comprehensive optimization strategy, it is hoped that blood availability in the community can be maintained on an ongoing basis and able to support optimal health services.